Fuzzy logic power management for a PV/Wind microgrid with backup and storage systems - Aysar M. Yasin; Mohammed F. Alsayed (International Journal of Electrical and Computer Engineering (IJECE), 2021)
This work introduces a power management scheme based on the fuzzy logic controller (FLC) to manage the power flows in a small and local distributed generation system. The stand-alone microgrid (MG) includes wind and PV generators as main power sources. The backup system includes a battery storage system (BSS) and a diesel generator (DG) combined with a supercapacitor (SC). The different energy sources are interconnected through the DC bus. The MG is modeled using MATLAB/Simulink Sim_Power System™. The SC is used to compensate for the shortage of power during the start-up of the DG and to compensate for the limits on the charging/discharging current of the BSS. The power balance of the system is the chief objective of the proposed management scheme. Some performance indexes are evaluated: the frequency-deviation, the stability of the DC bus voltage, and the AC voltage total harmonic distortion. The performance of the planned scheme is assessed by two 24-hours simulation sets. Simulation results confirm the effectiveness of FLC-based management. Moreover, the effectiveness of the FLC approach is compared with the deterministic approach. FLC approach has saved 18.7% from the daily load over the deterministic approach. The study shows that the quality of the power signal in the case of FLC is better than the deterministic approach.